Pengaruh Perputaran Persediaan dan Penjualan Terhadap Laba Bersih Pada Pertokoan PKP-RI Kota Sukabumi Tahun 2015-2019 - Luthfianinurri, Luthfianinurri (Universitas Muhammadiyah Tangerang, 2023)
This study aims to determine the effect of inventory turnover and sales on net income. The research method used is quantitative methods and data collection techniques in this study using secondary data sources in the form of observation studies, documentation and literature studies. The results showed that there was a partially positive effect between the independent variable inventory turnover (X1) on net income (Y) with a t-count value of 2.719 > 2.009 (t table of 55 data) with a significant value of 0.005 <0.05 and there was a positive effect. partially between the independent variable sales (X2) to the dependent variable net income (Y) with a t-count value of 7.982>2.006 (t table of 55 data) with a significance of 0.000 <0.05. There is a simultaneous positive effect between the independent variables inventory turnover (X1) and sales (X2) on the dependent variable net income (Y) simultaneously at PKP-RI Shops in Sukabumi City with an F calculated value of 116.747> 3.175 (F table of 55 data) with a significant value of 0.00 <0.05.